Quality of life among the elderly: The role of emotion regulation strategy and family social support - Alfi Purnamasari; Herlina Siwi Widiana; Erlina Listyanti Widuri (Universitas Ahmad Dahlan, 2026)
Indonesia has a population structure with a high elderly population. Therefore, a study of the quality of life among the elderly is needed. This study aimed to examine the role of emotion regulation strategies and family social support on the quality of life among the elderly. This study employed a quantitative approach using a cross-sectional research design. Forty-three elderly aged over 60 who live with their family in Yogyakarta Special Province participated. The data was collected by WHOQOL-BREF, Family Social Support Scale and Emotion Regulation Questionnaire. Results from the regression analysis show emotion regulation strategies, cognitive reappraisal and expressive suppression, and family social support simultaneously have a significant role in the quality of life among the elderly. By controlling family social support and emotion regulation strategy expressive suppression, there is a significant positive relationship between emotion regulation strategy cognitive reappraisal and quality of life among the elderly. There is also a significant positive relationship between family social support and quality of life among the elderly by controlling emotion regulation strategies. However, there is no significant relationship between emotion regulation strategy expressive suppression with quality of life among the elderly. The elderly need to apply cognitive reappraisal and get family social support to reach a quality of life.